LEARNING ENGLISH THROUGH AMERICAN FOLKLORE USING INTERACTIVE WEBSITE FOR JUNIOR HIGH SCHOOL STUDENTS - Wiharto, Dede (LANTERN (Journal on English Language, Culture and Literature), 2014)
The development of information technology has affected a lot of aspects in the world. One of the aspects that is influenced by the development is education aspect especially for its learning process. Learning process has transferred from offline to online using internet and computer technology. It is means that student can study and learn through website everywhere and anywhere without having to meet with their teachers. Website becomes popular learning media used by teacher to teach their students. This interactive website is a learning English website for Junior High School students. This website is available in two languages or bilingual in English and Indonesian Language. The reason why this website uses bilingual is because the target learners are in basic level. This website uses material of American Folklore for six language skills that are reading, writing, listening, speaking, grammar and translation. Blogspot.com is a provider hosting and domain for this website by the domain title “English is Fun with American Folklore”. It can be accessed in the address www.englishisfunwithamericanfolklore.blogspot.com. The aim of this interactive website is as learning media for Junior High School students to improve their skills in reading, writing, listening, speaking, grammar and translation.Website consists of three parts that are instruction, material and question. Instruction is the command for students about each section. The material consists of story from American Folklore in the form of text or audio or video. It is designed according to each section and lesson. Question part consists of questions for students after they study material. Questions are made in interactive type. It means that students can answer and get their grade or score directly on the website after all of questions are answered. Beside three parts above, this website is also provided with additional tools in order to help student to understand and learn material on each sections and answer questions. The tools include online dictionary, links to certain subject, links to vocabulary and meaning of the words etc.